Taking Tinkercad to the Next Level Enhance your ability to design, model, and 3D print with one of the most intuitive CAD programs - Erdreich, Jason; Erdreich, Jason (Packt Publishing, 2024)
Unleash your 3D design creativity with TinkerStar Jason Erdreich as he guides you through Tinkercad's advanced techniques, transforming your ideas into print-ready, unique creationsKey FeaturesImplement effective strategies for 3D modeling using constructive solid geometryLearn common 3D printing techniques and resources used in DIY and industrial settingsCreate functional and aesthetically pleasing 3D-printable objects for everyday use in the real-worldPurchase of the print or Kindle book includes a free PDF eBookBook DescriptionDiscover the user-friendly interface and versatility of Tinkercad and find out how it$1 (Bs revolutionizing digital creation. This comprehensive guide explores Tinkercad$1 (Bs 3D design features, equipping you with the skills to harness its full potential for advanced projects and creations. Written by a patented inventor and Tinkercad expert with over a decade of experience in technology education, this book offers an accessible, yet thorough approach to mastering Tinkercad for users of all levels. You'll enhance your 3D design skills as you delve into professional modeling topics and techniques in Tinkercad. As you progress, you$1 (Bll build your skills by mastering essential tools for 3D modeling, such as technical drawings and measurement methods, paving the way for efficient constructive solid geometry abilities. Advanced Tinkercad modeling techniques, including ruler and workplane tools, patterns, and shape generators, will guide you in bringing your designs to life through 3D printing. You'll also learn about advanced concepts such as tolerances, dimensions, material choice, and practical applications with step-by-step guides for creating items like threaded containers, puzzles, phone cases, and more. By the end of the book, you$1 (Bll be proficient in crafting intricate designs ready for successful production through 3D printing.What you will learnDiscover key techniques and strategies for developing 3D models using computer-aided design softwareNavigate advanced features and tools in the intuitive Tinkercad softwareHarness your own creativity and knowledge to expertly craft unique 3D models and creationsUnderstand the difference between common 3D printing techniques, and choose the best one for your needsTroubleshoot mistakes and become a more proficient makerApply your skills to identify problems, design solutions, and manufacture prototypes for the real worldWho this book is forIf you are a student, hobbyist, tinkerer, or maker familiar with the basic features of Tinkercad and want to learn how use it to create complex designs and models for 3D printing, this book is for you. While it focuses on intermediate and advanced techniques in Tinkercad, beginners looking to expand their CAD skills and explore 3D printing will also benefit. And don$1 (Bt worry if you don$1 (Bt have a 3D printer$1 (Bthis book is still for you!s